Kepurnakalaan dan Kepurnasthanaan: Merancang Pendidikan demi Masa Depan - Adiprasetya, Joas (Institut Agama Kristen Negeri Toraja, 2024)
This article aims to bring together Wendell Berry's educational concept and the concept of timefulness and placefulness based on the idea of the flourishing of life. Wendell Berry's educational theory and ecological philosophy will be used analytically and in dialogue with the theology of flourishing life. The conjoining of these two streams of thought will give rise to a futuristic model of education directed toward the future, which offers a sustainability perspective within the model of humanism and ecologism. Such a model of education is an alternative to an education controlled by technological innovation and political security. Artikel ini bertujuan untuk memperjumpakan konsep pendidikan Wendell Berry dan konsep kepurnakalaan dan kepurnasthanaan berbasis ide mengenai kehidupan yang mekar. Teori pendidikan dan filsafat ekologi Wendell Berry akan dipergunakan secara analitis dan didialogkan dengan teologi kemekaran hidup. Perjumpaan kedua arus pemikiran ini akan memunculkan sebuah model pendidikan yang terarah ke masa depan, yang berperspektif keberlanjutan di dalam model humanisme dan ekologisme. Model pendidikan semacam ini menjadi sebuah alternatif bagi sebuah pendidikan yang dikendalikan oleh inovasi teknologi dan keamanan politik.